Encyclopedia of artificial intelligence - Rabunal, Juan Ramon 1973-; Dorado, Julian 1970-; Pazos Sierra, Alejandro; Gale Group (Hershey, Penn. Information Science Reference, 2009)
Examines the most recent developments in the field covering theoretical developments, techniques, technologies, and applications of systems using intelligent characteristics for adaptability, automation learning, classification, prediction, and even artistic creation.
Volume I. Active learning with SVM - emulating subjective criteria in corpus validation -- Volume II. Energy minimizing active models in artificial vision - MREM, discrete recurrent network for optimization -- Volume III. Multilayer optimization approach for fuzzy systems - workflow management based on mobile agent technology.
Electronic reproduction.
Keywords: Artificial intelligence -- Encyclopedias; Artificial intelligence -- Research; Artificial intelligence -- Technological innovations; Electronic books